Orthopedic physical assessment - Magee, David J. (Philadelphia, Pennsylvania : Saunders, 2002)
The fourth edition is an update of information provided in the third edition along with major revisions to the introductory, shoulder, lumbar spine, and pelvic chapters as well as with a new chapter on amputee assessment.
Principles and concepts -- Head and face -- Cervical spine -- Temporomandibular joint -- Shoulder -- Elbow -- Forearm, wrist, and hand -- Thoracic (dorsal) spine -- Lumbar spine -- Pelvis -- Hip -- Knee -- Lower leg, ankle, and foot -- Assessment of gait -- Assessment of posture -- Assessment of the amputee -- Emergency sports assessment -- Preparticipation evaluation
Includes bibliographical references and index.
Keywords: ORTHOPEDICS -- DIAGNOSIS